Representações de uma comunidade escolar sobre o trabalho do professor de inglês: prescrição e reflexão - Cunha, Ana Maria Affonso (2008)
The purpose of this research is to investigate the representations of a school community concerning English teachers who have just taken the Reflection on Action course, bearing in mind what is actually realized from what is prescribed by the official law and by the school rules. This is a case study research, which involves, besides English teachers, other people who are involved in a school. The theoretical underpinnings for this study are: (a) Reflection, the theories which discuss this concept, specially the studies by Dewey (1933/1959) and Schön (1983, 1987, 1992), among others. (b) Representations, on the perspective by Moscovici (1981, 1989), Jodelet (2001), Celani and Magalhães (2002), Freire and Lessa (2003). (c) Ergonomics Approach, which brings the studies that involve the relationship between man and work, like the studies by Schwartz (1997, 1998, 2000), Clot (2000), Amigues (2002, 2004), Guerin et al (1991/2001), Souza-e-Silva (2003, 2004). (d) English Teaching in Brazil, according to the studies by Chagas (1957), Leffa (1999), Almeida Filho (2003), Paiva (2003). The data have been collected through two instruments: questionnaire and interview. The results made possible to characterize on the representations of a school community the prescriptions that are made, by the English teachers, the other participants, as well as the current view about English teaching in this setting. It was also observed that the educational practices still happen in the classroom. The results also allow to noticing that the relationship with the student is closer to the teachers than pedagogical action actually said